“Dosis de fertilizante con microorganismos benéficos (ferti em) en el cultivo de rabanito (raphanus sativus L.) en la provincia de Lamas” - Avila Silva, Lileth (2014)
This research work entitled "Dose of organic matter with beneficia! microorganisms (EM fert) in the cultivation of radish (Raphunus sativus L.) In The Province of Lamas" aimed to determine the best treatment effect of fertilizar enriched microorganisms (FERTI EM) cultivation of radish (Raphanus sativus L.) in the Province of Lamas, in the cultivation of Radish (Raphanus sativus L), workof This research was conducted in May 2014, the block design was used completely randomized, with 5 treatments and 3 blocks. Results obtained indicate that all the variables studied had a direct relationship with performance. The T 4 treatment (0.4 1 I ha) had the highest average with 18, 399.98 Kg.ha -1 in which performance and statistically surpassed others, followed by other treatments T3 (0.3 Kg/ha) T2 (0.2 Kg I ha) T1 (0.1 Kg I ha) and TO. Ali treatments yielded ratios B I C above zero being the treatment T4 (0.4 -1 Kg.ha microorganism (EM fertilization) scored the best B I C with 1.58 followed T3 (0.3 Kg I ha -1> ferti Microorganism (EM) T2 (0.2 Kg / ha -1> fertilization microorganism (EM), T1 (0.1 kg ha -1 > fertilization of microorganism (EM) and TO (control) with values of 1.44, 1.42 1.39 and 1.06 respectively. These results demonstrate that increasing doses of ferti microorganism (MS) directly repercuto increased performance and therefore Kg. ha -1 in increasing the profitability of growing Radish. Keywords: Radish, microorganismos, fert (EM)